Respon Pertumbuhan Stek Anggur (Vitis vinifera L.) terhadap Pemberian Beberapa Konsentrasi Ekstrak Bawang Merah (Allium ascalonicum L.) - Utami, Tri; Hermansyah, Hermansyah; Handajaningsih, Merakati (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2016)
The purpose of this study was to determine the optimum concentration of shallot extract to the growth of grape cuttings grape cuttings. This study was conducted from September to December 2015 in the city of Bengkulu. This research used Completely Randomized Design with a single factor and five replications. Treatment concentrations of 0% (control), shallot extract concentration of 25%, 75% and 100%. The variables measured were the time to sprout, shoot height, the number of leaves, number of roots, fresh weight and dry weight of cuttings. The results showed that the concentration of shallot extract 100% concentration enhances the growth of grape cutting, time to sprout, and the concentration of extract 50% increase shoot height and number of leaves on grape cuttings.